2020
DOI: 10.21055/0370-1069-2020-2-98-107
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and Historical-Geographical Analysis of <i>Yersinia pestis</i> Strains from Vietnam

Abstract: Objective of the work was to identify molecular-genetic peculiarities, to conduct whole genome sequencing and phylogenetic analysis of Yersinia pestis strains isolated inVietnam between 1962 and 1989.Materials and methods. We have studied the properties of 50 Y. pestis strains, carried out whole genome sequencing of 18 and fragment sequencing of 32 strains from Vietnam. Phylogenetic analysis was performed on the basis of whole genome SNPanalysis by 1391 identified SNPs. Whole genome SNP-analysis and search for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…1a and 2 ). A high-resolution phylogenetic tree, containing only 1.ORI2 strains showed that the five Vietnam strains 19 , 20 , isolated in 1962 (Saigon-Nhatraung-62-3), 1967 (140-Dalat), 1986 (P-13273, P-13272), and 1988 (P-14709) were grouped together and formed a distinct clade (Supplementary Figs. 1b and 2 , Supplementary Data 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…1a and 2 ). A high-resolution phylogenetic tree, containing only 1.ORI2 strains showed that the five Vietnam strains 19 , 20 , isolated in 1962 (Saigon-Nhatraung-62-3), 1967 (140-Dalat), 1986 (P-13273, P-13272), and 1988 (P-14709) were grouped together and formed a distinct clade (Supplementary Figs. 1b and 2 , Supplementary Data 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…кроме того, в литературе имеются данные, что штаммы ветви 1.ORI1 занесены с территории китая (гонконг) во вьетнам [8,11]. это подтверждают данные полногеномного секвенирования штаммов восточного биовара из вьетнама [12]. в работе G. Morelli et al с помощью филогенетического анализа показано существование девяти волн радиации ветви 1.ORI2: 1.ORI2а -берет свое начало в китае, откуда в 1896 г. на корабле из гонконга занесена в бомбей; 1.ORI2ii -распространилась по территории Юго-восточной азии; 1.ORI2iiiохватила северную африку (марокко, сенегал); 1.ORI2iv -распространилась в центральную и Южную африку; 1.ORI2v -характерна для Южной америки; 1.ORI2vi -была распространена в европе; 1.ORI2vii -еще одна линия эволюции в центральной и Южной африке; 1.ORI2viii -эта линия попала из индии в европу и оттуда в Южную америку; 1.ORI2ix -линия берет начало в китае, откуда привнесена во вьетнам и мьянму, после чего состоялся обратный занос из мьянмы в китайскую провинцию Юньнань [8,11].…”
unclassified